Selisik Semiotik Sosial dalam Konflik Komunikasi Opini Pejabat Publik di Media Sosial - Bambang Trimansyah; Mira Mirnawati (Ideas Publishing, 2022)
A post on Budi Santosa Purwokartiko's (BSP) Facebook timeline on April 27, 2022, caused a stir. Here's a BSP sentence that sparked a communication conflict: So, none of the 12 female college students I interviewed closed their heads in the style of desert humans. As an LPDP interviewer for students applying for scholarships, BSP is considered to have committed blasphemy against SARA. The BSP's post was also highlighted for his status as an official rector at the Kalimantan Institute of Technology. Through the qualitative research method of description, the author uses Halliday and Hasan's approach of social semiotic analysis to show signs/symbols of innuendo opinions from the BSP that have triggered communication conflicts between the BSP and the public.